The Constribution of Calligraphy Learning to Mahārah al-Kitābah At The Darul Ikhlas Islamic Boarding School - Nurfasilah, Nurfasilah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of calligraphy on learning Arabic (Maharah Al-Kitabah) at the Darul Ikhlas Islamic Boarding School. This research was conducted using descriptive qualitative research methods. The results of the research show that there is an influence of learning calligraphy on writing skills in Arabic subjects. Thus, it can be concluded that learning calligraphy has a significant effect on the ability to write in Arabic. The results of this research can be an important reference in efforts to improve Arabic language learning, especially in the maharah al-kitabah aspect. Apart from that, this conclusion can also be a basis for developing more effective learning methods in educational institutions that focus on teaching Arabic, especially related to Maharah al-Kitabah.Keyword: Calligraphy, Arabic, Mahārah Al-Kitābah